TRANSFORMING CONSCIOUSNESS THROUGH MEDITATION AND MINDFULNESS: THE PATH TO EMOTIONAL BALANCE AND MENTAL HEALTH - Zulaikah, Enik; Khamami, Akhmad Rizqon; Maftukhin, Maftukhin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to examine how transforming consciousness through meditation and mindfulness practices can contribute to emotional balance and individual mental health. The background of this research is based on the increasing global psychological problems, such as stress, depression, anxiety, and burnout, which are widely experienced by modern society. Meditation and mindfulness are seen as alternative and complementary methods that can foster self-awareness, reduce emotional reactivity, and build inner balance. The research method used is a Systematic Literature Review (SLR) by examining international scientific articles published in the last ten years. The selection process was carried out through searches in indexed databases such as Scopus, Web of Science, and Google Scholar with the keywords "meditation," "mindfulness," "emotional balance," and "mental health." The selected articles were then analyzed thematically to identify patterns, findings, and their relevance to the research topic. The results show that meditation and mindfulness contribute significantly to improving emotional balance, reducing symptoms of depression and anxiety, and strengthening mental health. The findings also confirm that mindfulness practices can be integrated into various fields, such as psychological therapy, education, and stress management in the workplace. The discussion underscores the importance of consistency of practice as well as environmental support in ensuring the effectiveness of this practice. The conclusions of this study confirm that transforming consciousness through meditation and mindfulness not only impacts individual mental health but also strengthens social relationships and improves overall quality of life. The practical implication is that meditation and mindfulness need to be more widely adopted as holistic mental health strategies that are affordable, sustainable, and adaptable to the challenges of modern life..